Assistance Of The Jangek Mr. Ali Kerupuk Small And Medium Enterprse (Sme) In The Pandemic Time Covid 19 - Debi Setiawan; Felix Irwan; Ramalia Noratama Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
Pak Ali Skin Crackers is one of the small businesses running in Teluk Kenidai Village, Kampar District. During the pandemic, Indonesia has seen a decline in the economic transaction, which results in the rise of furlough. To Addressing this issue, assistance is given to the Pak Ali skin cracker business to increase its productivity. This measure aims to improve the quality of the products in packaging and branding to be more interested in buying or distributing them to others. Increasing sales online is also seen as a practical solution during the pandemic. Maintaining a healthy lifestyle is also prioritized as the healthy work environment would likely affect productivity during the pandemic. Such community empowerment could be a threshold in improving the community's economy, transforming it from traditional to modern, and promoting healthy sales during this COVID outbreak. The methods used are preparation, main activity, and report. The results of this assistance are in the form of photos and target achievements.